2015
DOI: 10.3846/20294913.2015.1033663
|View full text |Cite
|
Sign up to set email alerts
|

Technological Assimilation and Divergence in Times of Crisis

Abstract: Abstract.We study an endogenous stochastic growth model whose dynamic evolution is determined by an adaptive learning process defining the accumulation of technological knowledge within countries. Both the assimilation of technological knowledge and the arrival rate of innovations depend on the technological development level of countries. We illustrate how heterogeneous levels of technological development provide laggard countries with insufficient innovation incentives, leading to divergences in total factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…1). A fundamental look at the change of technological wave lets us measure and forecast processes of long-termed economic and technological progress on the future based on retrospective analysis and established patterns [6]. However, this view of technological waves is not enough for management purposes [7].…”
Section: The Results Of the Researchmentioning
confidence: 99%
“…1). A fundamental look at the change of technological wave lets us measure and forecast processes of long-termed economic and technological progress on the future based on retrospective analysis and established patterns [6]. However, this view of technological waves is not enough for management purposes [7].…”
Section: The Results Of the Researchmentioning
confidence: 99%
“…The innovation system influences the division of skilled labor between production and innovation activities. Depending on the development course, the innovation system changes over time (Alvarez et al, 2016). Analyses have shown that GDP per capita is significantly influenced by a high level of employee education (Mihi-Ramirez et al, 2020).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…That is, technology and innovation are considered in a set of key factors of economic security. In addition to existing scientific publications, research in [7] reflects that the high innovative and technological development of each country stimulates the productivity of social labor. That is, the growth of technological development of the country stimulates its strengthening, provides economic security.…”
Section: A Theoretical-applied Model Has Been Built For Analyzing Ind...mentioning
confidence: 99%